Electronic structure and ferromagnetism of polycrystalline Zn1-xCoxO (0 <= x <= 0.15) - Deka, Sasanka; Joy, Pattayil Alias (Solid State Communications, 2005)
The electronic structure of polycrystalline ferromagnetic Zn1-x,CoxO (0.05 <= x <= 0.15) and the oxidation state of Co in it, have been investigated. The Co-doped polycrystalline samples are synthesized by a combustion method and are ferromagnetic at room temperature. XPS and optical absorption studies show evidence for Co2+ ions in the tetrahedral symmetry, indicating, substitution of Co2+ in the ZnO lattice. However, powder XRD and electron diffraction data shock the presence of Co metal in the samples. This give evidence to the fact that some Co2+ ion are incorporated in the ZnO lattice which gives changes in the electronic structure whereas ferromagnetism comes from the Co metal impurities present in the samples. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Magnetically ordered materials; Optical properties; Semiconductors

On the structural, magnetic and electrical properties of sol-gel derived nanosized cobalt ferrite - Gopalan, E. Veena; Joy, Pattayil Alias; Al-Omari, I. A.; Kumar, D. Sakthi; Yoshida, Yasuhiko; Anantharaman, Maliemadom R. (Journal of Alloys and Compounds, 2009)
Nanoparticles of cobalt ferrite were synthesized by sol gel method. These particles were structurally characterized by using X-Ray Diffraction and Transmission Electron Microscopy, High Resolution Transmission Electron Microscopy, Energy Dispersive Spectrum and Inductively Coupled Plasma Analysis and the results confirmed the formation of spherically shaped nanoparticles of cobalt ferrite having a size lying in the range of 13-14 nm. The as prepared sample was sintered at 800 degrees C and the structural, magnetic and dielectric properties were measured. The dielectric properties were studied and analyzed as a function of temperature and frequency. The ac and dc conductivity studies were carried out to delve into the conduction mechanism. The existing models based on quantum mechanical tunneling were effectively employed to explain the frequency dependent conductivity. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Electronic Transport; Magnetic measurements; Magnetically ordered materials; Nanostructures; Scanning and transmission electron microscopy; Sol-gel synthesis; X-ray diffraction